Identification and characterization of a recombinant cysteine peptidase (AsCathL) from leaf-cutting ant Atta sexdens Linnaeus, 1758 (Hymenoptera, Formicidae) - Santos Correa, Katia Celina; Moreira, Ariele Cristina; Abd El-Raheem Ibrahim, Amr Galal; Ramos de Jesus, Hugo César; Micocci, Kelli Cristina [UNESP]; Crizóstomo Kock, Flávio Vinícius; Bueno, Odair C. [UNESP]; Venâncio, Tiago; Henrique-Silva, Flávio; Souza, Dulce Helena F. (Elsevier, 2023)
Cysteine peptidases are involved in physiological processes of insect development and have been considered as potential targets for the development of insect control strategies. In this study, we obtained a recombinant cysteine cathepsin L (AsCathL) from leaf-cutting ant (Atta sexdens), a species from the order Hymenoptera who causes enormous damage to crops, natural forests and reforested areas. RT-qPCR showed AsCathL expression throughout insect development and in all body parts of the adult insect analysed, suggesting its role as a lysosomal cathepsin. AsCathL encodes a protein of 320 amino acid residues consisting of a pro-peptide and the mature with amino acids sequence over 67% similarity with lysosomal cathepsin L of species from Lepidoptera and Diptera. Phylogenetic tree revealed that AsCathL is very similar to predicted cathepsins found in other ants. Recombinant AsCathL was expressed in insoluble form by Escherichia coli Arctic Express (DE3) RIL, purified under denaturing conditions and refolded. The enzyme showed hydrolytic activity in vitro towards synthetic substrate Z-Phe-Arg-AMC at acidic pH. Synthetic inhibitor E−64 acted against peptidase activity and a study regarding the interaction between E−64 and AsCathL using nuclear magnetic resonance (NMR) revealed that 83.18% from all E−64 molecules are irreversibly bound to AsCathL. In addition, the proteolytic activity of AsCathL was strongly inhibited by recombinant sugarcane cystatins with Ki ranging from 0.6 nM to 2.95 nM. To the best of our knowledge this is the first report characterizing a cysteine peptidase from leaf-cutting ants, which may contribute to future studies of ants’ cathepsins.
Keywords: Atta sexdens; Cysteine cathepsin; Cysteine peptidase; Insect cathepsin; Sugarcane cystatin